2000
DOI: 10.1007/bf02802634
|View full text |Cite
|
Sign up to set email alerts
|

Therapy and drug resistance in malaria

Abstract: The aim of this study was to highlight the high degree of clinical resistance of P. falciparum and also of P. vivax to chloroquine and also the importance of early diagnosis and prompt treatment. Ninety cases of smear positive malaria aged between 6 months to 14 years were studied with regards to clinical manifestations, management and outcome. Criteria for drug resistance were absence of clearance of parasitemia and/or persistance of fever after 72 hours of therapy. Chloroquin resistance was noted in 15 (62.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…CQ is the first-line treatment for P. vivax malaria in India but the exact burden of CQR P. vivax in India is unclear. Since India has already declared its aim to eliminate malaria by 2030 [ 28 ], the detection and monitoring of CQR P. vivax are crucial. In this systematic review, CQ therapeutic efficacy was assessed by in vivo efficacy studies ( n = 1787) and ex-vivo ( n = 141) studies from different malaria-endemic regions in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CQ is the first-line treatment for P. vivax malaria in India but the exact burden of CQR P. vivax in India is unclear. Since India has already declared its aim to eliminate malaria by 2030 [ 28 ], the detection and monitoring of CQR P. vivax are crucial. In this systematic review, CQ therapeutic efficacy was assessed by in vivo efficacy studies ( n = 1787) and ex-vivo ( n = 141) studies from different malaria-endemic regions in India.…”
Section: Discussionmentioning
confidence: 99%
“…The poor response could have been due to poor CQ absorption in malnourished patients as well. Another study conducted by Kulkarni et al [ 28 ] similarly reported a high prevalence of treatment failures (51.7%) from Mumbai. However, the study’s sample size was very small ( n = 29) and the duration of follow-up was very short (less than 7 days).…”
Section: Discussionmentioning
confidence: 99%
“…The development of drug resistance in pathogenic fungi and parasites, such as resistance to azoles, which are inhibitors of the ergasterol sterol biosynthesis enzyme Erg11 in the pathogenic yeast Candida albicans [32][33][34], or resistance to chloroquine and mefloquine in the malarial parasite Plasmodium falciparum, [35][36][37][38] illustrates the enormous public health impact of fungal drug resistance.…”
Section: Effects Of Hsp90 Inhibitors On Drug Resistance In Pathogenmentioning
confidence: 99%